ANALISIS KONSEPTUAL ORGANISASI PEMBELAJARAN (LEARNING ORGANIZATION) SEBAGAI TEORI ORGANISASI KONTEMPORER - Edah Jubaedah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2010)
In the era of accelerated globalization and knowledge economy, learning organizations, with their flexibility in adapting to fast and complex changes, have drawn close attention from the academic and industrial communities. Now, various organizations, private or public, make it their goal to transform themselves into learning organizations. Organization by building a learning organization can accelerate and strengthen the dissemination and application of information and knowledge so that the organization can promptly gain insight into new trends, opportunities, ideas, knowledge, and information, to enhance its capabilities. Inaddition, a learning organization encourages innovation and competition so that the it can break away from outmoded conventions and have unfailing impetus for reform and innovation in terms of their ways of thinking, administrative technologies andmethods, and administrative institutions.